Kewenangan Majelis Kehormatan Notaris Wilayah Dalam Pemeriksaan Notaris Yang Pindah Wilayah Jabatan Oleh Aparat Penegak Huku - Rahman, Ahmad Laduni Arif; Sesung, Rusdianto (Al-Jinayah: Jurnal Hukum Pidana Islam, 2018)
Abstract: The exercise of authority of the Regional Notary Honorary Council in approving and / or rejecting applications for approval from law enforcement (investigators, public prosecutors, or judges) against a notary who has moved the area of ​​office related to the deed made. These involved in a criminal case raises 2 (two) the fundamental question related to the authority of the Regional Notary Honorary Council which is authorized to approve and / or reject the application for approval and determination of the time limit no later than 30 (thirty) working days for the Regional Notary Honorary Council provides an answer. From the results of the study, it is known that based on the laws and regulations, the authority to give approval to Notaries who moved to the position of office against the request of law enforcement officers was the authority of the notary council in the notary area concerned. This means that the provisions apply mutatis mutandis to the determination of the time limit no later than 30 (thirty) working days for the Regional Notary Honorary Council to provide answers as of the receipt of summons by law enforcement officers. Keywords: Authority, Regional Notary Honorary Council, notary, Law Enforcement Officials.   Abstrak: Pelaksanaan kewenangan Majelis Kehormatan Notaris Wilayah dalam memberikan persetujuan dan/atau penolakan permohonan persetujuan dari penegak hukum (penyidik, penuntut umum, atau hakim) terhadap notaris yang telah pindah wilayah jabatan berhubungan dengan akta yang dibuatnya tersangkut perkara pidana, menimbulkan 2 (dua) pertanyaan mendasar berkaitan dengan kewenangan Majelis Kehormatan Notaris Wilayah yang berwenang memberikan persetujuan dan/atau penolakan permohonan persetujuan dan penentuan batasan waktu paling lama 30 (tiga puluh) hari kerja bagi Majelis Kehormatan Notaris Wilayah memberikan jawaban. Dari hasil penelitian diketahui bahwa berdasarkan peraturan Perundang undangan, kewenangan memberikan persetujuan terhadap Notaris yang pindah wilayah jabatan terhadap permohonan aparat penegak hukum adalah kewenangan Majelis Kehormatan notaris wilayah tempat kedudukan notaris yang bersangkutan. Artinya ketentuan tersebut berlaku secara mutatis mutandis terhadap penentuan batasan waktu paling lama 30 (tiga puluh) hari kerja bagi Majelis Kehormatan Notaris Wilayah memberikan jawaban terhitung saat penerimaan surat pemanggilan oleh aparat penegak hukum. Kata Kunci: Kewenangan, Majelis Kehormatan Notaris Wilayah, Notaris, Aparat Penegak Hukum.